Micro-Determination of Palladium Using 2,6-Bis(1-hydroxy-2-naphthylazo)pyridine as an Analytical Ragent - Singh Kadyan, Pratap; Singh, Devender; Singh, Ishwar (Asian Journal of Chemistry, 2012)
A simple, selective and sensitive spectrophotometric method was developed for the micro-determination of palladium(II) using 2,6-bis(1-hydroxy-2-naphthylazo)pyridine (PBN). Alcoholic solution of 2,6-bis(1-hydroxy-2-naphthylazo)pyridine formed two complexes with palladium(II) at different pH, a green coloured complex having lmax 650 nm in the pH range 3.5-5.0 and a reddish-brown complex absorbing maximum at 570 nm in the pH range 7.5-9.0 on warming for ca. 5 min on a water bath. At pH 3.5-5.0, the green coloured Pd(II)-PBN complex had molar absorptivity and Sandell's sensitivity 1.06 × 104 L mol-1 cm-1 and 0.010 μg cm-2, respectively. The validity of the Beer's law was followed upto 14 ppm with an optimum concentration range for accurate determination of 0.8-12.5 ppm. The molar composition of the complex was 1:1 (M:L) as determined by Job's method of continuous variations. In the pH range 7.5-9.0, the reddish-brown Pd(II)-PBN complex had molar absorptivity of 1.0 × 104 L mol-1 cm-1 showing the Sandell's sensitivity of 0.010 μg cm-2. Beer's law was followed upto 11.8 ppm with the optimum concentration range of 0.8-10.5 ppm. The reddish-brown complex had the molar composition of 1:2 (M:L). A number of foreign ions tested for their interferences and use of masking agents whenever necessary were investigated during the micro-determination of palladium(II). Analytical method established at low pH showed good sensitivity and its application was extended to determine Pd(II) in some synthetic solutions equivalent to that of some alloys, hydrogenation catalyst etc.